Alcohol consumption in the Australian coal mining industry. Issue 4 (31st October 2016) - Tynan, Ross J; Considine, Robyn; Wiggers, John; Lewin, Terry J; James, Carole; Inder, Kerry; Kay-Lambkin, Frances; Baker, Amanda L; Skehan, Jaelea; Perkins, David; Kelly, Brian J
Abstract : Objectives: To investigate patterns of alcohol use within the coal mining industry, and associations with the personal, social, workplace and employment characteristics. Design: 8 mine sites across 3 eastern Australian states were surveyed, selected to encompass key geographic characteristics (accessibility and remoteness) and mine type (open cut and underground). Problematic alcohol use was measured using the Alcohol Use Disorders Identification Test (AUDIT) to determine: (1) overall risky or hazardous drinking behaviour; and (2) frequency of single-occasion drinking (6 or more drinks on 1 occasion). Results: A total of 1457 employees completed the survey, of which 45.7% of male and 17.0% of female participants reported levels of alcohol use within the range considered as risky or hazardous, considerably higher than the national average. Hierarchical linear regression revealed a significant contribution of many individual level factors associated with AUDIT scores: younger age, male, current smoking status; illicit substance use; previous alcohol and other drug use (AOD) problems; and higher psychological distress. Workplace factors associated with alcohol use included working in mining primarily for the high remuneration, and the type of mining, with underground miners reporting higher alcohol use than open-cut miners. Conclusions: Our findings provide support for the need to address alcohol use in the coal mining industry over and above routine on-site testing for alcohol use.